Indications and outcomes of penetrating keratoplasty at a tertiary care hospital in northern Thailand - R. Khotcharrat (2020)
© 2019 Medical Association of Thailand. All rights reserved. Objective: To inquire into the causative diseases for corneal transplantation, treatment outcomes, and the prognostic factors influencing post-operative outcomes. Materials and Methods: A retrospective review of the medical records of the patients that underwent penetrating keratoplasty between September 1, 2004 and December 31, 2009 was done. Results: Corneal transplantation was done in 51 eyes of 51 patients with a mean age of 60.9±14.3 years (range from 25 to 88 years old). The most common indication was for optical purpose (82.4%) in patients diagnosed with bullous keratopathy (n=14, 25.9%), followed by corneal scar (n=10, 18.5%). The pre-operative mean visual acuity was 2.3±0.7 Log MAR, and postoperative mean visual acuity was 1.6±0.9 Log MAR. The mean of visual improvement was 0.7±0.8 Log MAR (p=0.001). The graft failure rate was 48%, caused by irreversible graft rejection, recurrent infection, corneal ulcer on graft, graft perforation, and late endothelial failure. The risk of graft failure was significantly higher in patients with pre-existing glaucoma, re-grafting for previous graft failure, and secondary post-operative glaucoma. Conclusion: Penetrating keratoplasty remains the effective treatment in many corneal conditions. Bullous keratopathy and corneal scar are the major indications for optical purpose.